2002
DOI: 10.1109/16.998603
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the CoolMOS/sup TM/ transistor - Part I: Device physics

Abstract: Abstract-CoolMOS™ is a novel power MOSFET with a "superjunction" for its drift region, which results in a vastly improved relationship between the on resistance and breakdown voltage. The presence of the superjunction makes the device physics very interesting and complicated. In this paper, we present simulation results aimed at understanding the device operation both in the on state and in the off state. Quasi saturation of the drain current is analyzed, and it is shown that it can be prevented by increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Physically, the drift region behavior suggests a model with two JFETs in series, one for the "neck" region and the other for the "pillar" region. Analytical modeling of the "pillar" part of the drift region was also done in [8], which confirmed that its -equation is similar to that of a JFET. The structure of the CoolMOS™ transistor and simulation results described in [8] series with a "neck" JFET, followed by the "pillar" JFET.…”
Section: Basic Modelmentioning
confidence: 54%
See 4 more Smart Citations
“…Physically, the drift region behavior suggests a model with two JFETs in series, one for the "neck" region and the other for the "pillar" region. Analytical modeling of the "pillar" part of the drift region was also done in [8], which confirmed that its -equation is similar to that of a JFET. The structure of the CoolMOS™ transistor and simulation results described in [8] series with a "neck" JFET, followed by the "pillar" JFET.…”
Section: Basic Modelmentioning
confidence: 54%
“…A simple model was first developed, based on simulation results obtained with PISCES [8]. The simulated device is shown in Fig.…”
Section: Basic Modelmentioning
confidence: 99%
See 3 more Smart Citations